Efficacy of treatment intensity in German-speaking children with childhood apraxia of speech. (February 2022) - Leonhartsberger, Sabine; Huber, Eva; Brandstötter, German; Stoeckel, Ruth; Baas, Becky; Weber, Christoph; Holzinger, Daniel
Motor learning principles guide treatment of childhood apraxia of speech (CAS). Previous studies found children to benefit from higher-intensity conditions; however, they did not control for the total amount of therapy time. The aims of the article are to examine the effects of high versus low treatment frequency in intervention for CAS in German-speaking children. An alternating single-subject design with multiple baselines was applied to compare frequent, short sessions with fewer, longer sessions in terms of speech production accuracy in four children with CAS while keeping the total therapy time constant. We administered a version of integral stimulation treatment. Despite inter-individual differences, changes under both treatment conditions showed similar positive trajectories for all four children. Untreated control targets also improved across participants and conditions. Maintenance and generalization to untreated targets were observed two weeks and three months post treatment, independent of treatment intensity. Our results show no significant advantage of more intensive treatment when the total therapy time is held constant. This study contributes to the evidence base for the use of integral stimulation in treating children with CAS, and in particular those who speak languages other than English.